Remotely Assessing Symptoms of Parkinson's Disease Using Videoconferencing: A Feasibility Study. (26th December 2016) - Stillerova, Tereza; Liddle, Jacki; Gustafsson, Louise; Lamont, Robyn; Silburn, Peter
Abstract : Purpose. To evaluate the feasibility of assessing a person's symptoms of Parkinson's disease (PD) in their home using the videoconferencing technology they already possess, without a home visit. Method. Eleven participants with PD completed the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) face-to-face and then via videoconferencing within a two-week period. Participants used free software and the computers and webcams available at their home to complete the videoconference assessment with a clinical rater scoring remotely. Clinical raters and participants provided feedback on the experience. Results. Excluding rigidity and postural stability, between zero and seven items could not be completed in the assessment of each participant (median 2.0, IQR 1.0–4.0). Between face-to-face and videoconference assessments, the median difference in scores was 3.0 (IQR 1.5–9.0). Content analysis of feedback identified the clinical raters' reasons why some scoring could not be completed and the participants' hope for future clinical application. Conclusions . In using free everyday technology available in participants' homes, MDS-UPDRS ratings could be obtained without an initial home visit; however some items were unable to be scored for some participants. Use of a protocol or technological advances are likely to reduce missing items.